IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) RELATED TO SUSTAINABLE TOURISM DEVELOPMENT IN BANGKALAN REGENCY - Purwanto, Hery; Prasetyo, Alvin Sugeng; Firmansyah, Yacob Juan; Anisah, Siti; Aini, Qurra Aitul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Sustainable Development Goals (SDGs) are a global agenda for sustainable development. Tourism and sustainable development cannot be separated, these two things help each other. The aim of this research is to: 1. Analyze the implementation of SDGs in developing sustainable tourism in Bangkalan district, and 2. Analyze the role of multi-stakeholders in developing sustainable tourism, 3. Analyze the policies implemented by the Bangkalan Regency Government in developing sustainable tourism. The type of research used in this research is qualitative descriptive research, with a case study approach. The results of this research are (1) The implementation of SDGs in developing sustainable tourism in Bangkalan district is actually already visible but needs to be expanded to other tourist destinations. Apart from that, it needs to be expanded, both marine and land ecosystem-based tourism. (2). The role of multi-stakeholders in developing sustainable tourism is not yet fully visible. Collaboration that is able to connect elements of business, government, academic community, media so that sustainable tourism can be realized. Attention and commitment from multi-stakeholders is needed, especially the Bangkalan district government. Collaboration between actors, between sectors and between lines in tourism development must be maintained in a sustainable and integrated manner. (3). The policies implemented by the Bangkalan Regency Government in developing sustainable tourism are contained in several documents, including: 1. Regional Medium Development Plan (RPJMD) 2018-2023, 2. Regency Tourism Development Master Plan (RIPPARKAB), and 3. Regional Innovation System (SIDa) . Current policy emphasizes the development of cultural and culinary-based tourism as an effort to improve the community's economy